Effects of quercetin and vitamin E on ovariectomy-induced oxidative stress in rat serum and tibia - Vakili, Sina; Zal, Fatemeh; Mostafavipour, Zohreh; Savardashtaki, Amir; Jafari Khorchani, Majid; Hassanpour, Ashraf (Archives of Biological Sciences, 2020)
Paper description: Estrogen deficiency after ovariectomy induces an imbalance between the production of reactive oxygen species and the antioxidant defense system, leading to oxidative stress and resulting complications. Administration of either quercetin or vitamin E improved oxidative stress in ovariectomized rats. However, the coadministration of quercetin and vitamin E had a weaker improving effect than when either compound was applied alone. Ovariectomy-induced oxidative stress could be ameliorated by administration of either quercetin or vitamin E and could alleviate ovariectomy-induced dysfunction. Abstract: Estrogen deficiency after menopause accelerates redox imbalance, leading to oxidative stress (OS) and other postmenopausal complications such as osteoporosis and cardiovascular disease. In the present study, the effects of quercetin (Q), vitamin E (vitE) and estradiol (E2) on the oxidative status in ovariectomized (OVX) rats were investigated. OVX animals were treated with Q (15 mg/kg/day), vitE (60 mg/kg/day), E2 (10 µg/kg/day) and Q (7.5 mg/kg/day)+vitE (30 mg/kg/day) for 10 weeks. OS markers were analyzed in the serum and tibia of rats. Data indicated that after ovariectomy, rats exhibited a reduction in serum and tibia antioxidants and elevation of oxidant markers. The activities of antioxidant enzymes (AOEs), glutathione peroxidase (GPx), catalase (CAT) and glutathione reductase were decreased and the glutathione (GSH) content was reduced, whereas the malondialdehyde (MDA) level was increased. Treatment with Q, vitE and E2 markedly reversed these changes and improved OS. In conclusion, prevention by antioxidant agents, including Q and vitE, could be a potential approach in the management of menopause-related complications. https://doi.org/10.2298/ABS191115003V Received: November 15, 2019; Revised: December 15, 2019; Accepted: January 13, 2020; Published online: January 20, 2020 How to cite this article: Vakili S, Zal F, Mostafavipour Z, Savardashtaki A, Jafari Khorchani M, Hassanpour A. Effects of quercetin and vitamin E on ovariectomy-induced oxidative stress in ratserum and tibia. Arch Biol Sci. 2020;72(1):95-104.